Crescimento pró-pobre no Nordeste do Brasil: uma análise dos períodos (1991-2000 e 2000-2010) - Neto, Raul da Mota Silveira (2014)
This paper analyses the quality of economic growth of the Brazilian Northeast region,the poorest region of the country, during the period 1991-2010 specifically investigatingthe relative benefices of poor individuals. By using an indicator that considersboth traditional poverty measures and the relative growth of the income from poorestindividuals, it provides evidence for the states and mesorregions of the Brazilian Northeast.The set of evidence indicates that the results for the periods 1991-2000 and2000-2010 are very different: during the second period the income dynamic is clearlyfavorable to poorest individuals; during the first, the opposite situation is observed.Focusing on the labor income, instead of on total income, allows to identify the betterperformance of the mesorregions that includes the Metropolitan Region of Northeast.